2013
DOI: 10.1177/2325967113505739
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes After Arthroscopic Scapulothoracic Bursectomy and Partial Superomedial Angle Scapulectomy

Abstract: Background:Arthroscopic scapulothoracic bursectomy with partial superomedial angle scapulectomy has been described as a treatment for persistent scapulothoracic bursitis with varying results.Purpose:To evaluate patients after arthroscopic scapulothoracic bursectomy utilizing validated functional outcome instruments.Study Design:Case series.Methods:Fifteen patients underwent arthroscopic scapulothoracic bursectomy and partial superomedial angle scapulectomy. Thirteen patients were available for review at a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Five studies 13 , 23 , 35 , 41 , 47 reported VAS pain scores on a 0 to 10 scale. All improved postoperatively, from a mean of 6.9 ± 0.7 to a mean of 1.9 ± 0.9.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies 13 , 23 , 35 , 41 , 47 reported VAS pain scores on a 0 to 10 scale. All improved postoperatively, from a mean of 6.9 ± 0.7 to a mean of 1.9 ± 0.9.…”
Section: Resultsmentioning
confidence: 99%
“…These studies investigated a combination of open and endoscopic scapulothoracic bursectomy, pectoralis minor tendon release, and partial scapular resection. The most commonly reported functional outcome scores were the American Shoulder and Elbow Surgeons (ASES) score (6 studies), 23 , 25 , 26 , 35 , 41 , 47 and the simple shoulder test (SST, 4 studies). 23 , 27 , 35 , 47 Mean ASES scores improved from 50.3 ± 12.2 to 80.6 ± 14.9 postoperatively, and SST scores from 5.6 ± 1.0 to 10.2 ± 1.1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However there are limitations to this approach. These include increased initial pain, large incisions with subsequent scarring, a requirement for rhomboid muscle detachment and the need for postoperative immobilization [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%